2006
DOI: 10.1124/dmd.104.003202
|View full text |Cite
|
Sign up to set email alerts
|

IN VITRO METABOLISM OF FERROQUINE (SSR97193) IN ANIMAL AND HUMAN HEPATIC MODELS AND ANTIMALARIAL ACTIVITY OF MAJOR METABOLITES ON PLASMODIUM FALCIPARUM

Abstract: ABSTRACT:Ferroquine (SSR97193) has been shown to be a promising antimalarial, both on laboratory clones and on field isolates. So far, no resistance was documented in Plasmodium falciparum. In the present work, the metabolic pathway of ferroquine, based on experiments using animal and human hepatic models, is proposed. Ferroquine is metabolized mainly via an oxidative pathway into the major metabolite mono-N-demethyl ferroquine and then into di-N,N-demethyl ferroquine. Some other minor metabolic pathways were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 23 publications
1
39
0
Order By: Relevance
“…The biotransformation of FQ has been recently studied in vitro in animal and human models. 11 Even if mono-N-desmethyl-and di-N,N-desmethyl-FQ showed a decreased in vitro activity compared to the parent molecule, they remained more active than CQ on P. falciparum CQ-resistant strains. 11,28 It is notably that the metabolites of CQ showed no activity against CQ-resistant strains.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The biotransformation of FQ has been recently studied in vitro in animal and human models. 11 Even if mono-N-desmethyl-and di-N,N-desmethyl-FQ showed a decreased in vitro activity compared to the parent molecule, they remained more active than CQ on P. falciparum CQ-resistant strains. 11,28 It is notably that the metabolites of CQ showed no activity against CQ-resistant strains.…”
Section: Resultsmentioning
confidence: 99%
“…11 Even if mono-N-desmethyl-and di-N,N-desmethyl-FQ showed a decreased in vitro activity compared to the parent molecule, they remained more active than CQ on P. falciparum CQ-resistant strains. 11,28 It is notably that the metabolites of CQ showed no activity against CQ-resistant strains. The dramatic activity of FQ metabolites against CQ-resistant P. falciparum parasites growth enables us to expect a long-acting antimalarial activity during chemotherapy of malaria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro drug susceptibility testing has demonstrated that several hydroxamate-based HDAC inhibitors are potent inhibitors (IC 50 s in low nanomolar concentrations) of laboratory strains of P. falciparum and, importantly, display promising selectivity for malaria parasites versus mammalian cell lines (Ͼ100 fold), depending on the inhibitor and cell lines used (2,12). H͔hypoxanthine incorporation) as previously published for chloroquine (8,9), amodiaquine (1,19), piperaquine (1, 30), mefloquine (1, 10), artesunate (1, 10) (the chloroquine-sensitive and -resistant lines were 3D7 and K1, respectively), SAHA (12), 2-ASA-9 (2), and 2-ASA-14 (2) (the chloroquine-sensitive and -resistant laboratory lines, respectively, were D6 and W2 for SAHA and 3D7 and Dd2 for 2-ASA-9 and 2-ASA-14 In the present study, we compared the ex vivo activities of three hydroxamate-based HDAC inhibitors against multidrugresistant clinical isolates of P. falciparum and P. vivax. This is the first report of antimalarial activity of this class of compounds directly against clinical isolates and against P. vivax parasites.…”
Section: Discussionmentioning
confidence: 99%